ACADEMIC ENGAGEMENT IN RELATION TO ACADEMIC RESILIENCE: A STUDY OF UNDERGRADUATE STUDENTS - Haldar, Rana; Kumar, Kishor (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research has mainly aimed to study the academic engagement and academic resilience of undergraduate students and to determine the relationship between academic engagement of undergraduate students and their academic resilience. The study was confined on a sample of 228 undergraduate students of Nadia and Purba Bardhaman districts of West Bengal (India). The self-developed ‘Academic Engagement Scale’ and ‘Academic Resilience Scale’ were used by the researchers to study the level of academic engagement and academic resilience. The findings of the study revealed that a significant difference has been found between the mean scores of academic engagement of undergraduate students with respect to their locality and programme streams i.e. science & arts; mean scores of academic resilience of undergraduate students with respect to their locality; high and low academic engagement groups of undergraduate students on the measures of their academic resilience levels. But no significant difference has been found between the mean scores of academic engagement of undergraduate students with respect to their gender; and the mean scores of academic resilience with respect to their gender and academic streams i.e. science and arts stream. Further, a significant relationship has been found between the academic engagement of undergraduate students and their academic resilience.